Policies for African Development : From the 1980s to the 1990s. (Washington, D.C. : International Monetary Fund, 1992)
Despite economic hardships during the past 20 years, Africa has recently enjoyed positive real economic growth, transformed its economic structures and systems, and improved living standards. Much of this owes to the determined pursuit of growth-oriented adjustment efforts, with IMF support, by nearly 30 African countries. Edited by I.G. Patel, this volume discusses progress made by Africa in the 1980s and prospects and needs for continued development in the 1990s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet